2019
DOI: 10.1104/pp.19.00972
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Localization in Plant Cells

Abstract: Localization of mRNAs at the subcellular level is an essential mechanism for specific protein targeting and local control of protein synthesis in both eukaryotes and bacteria. While mRNA localization is well documented in metazoans, somatic cells, and microorganisms, only a handful of well-defined mRNA localization examples have been reported in vascular plants and algae. This review summarizes the function and mechanism of mRNA localization and highlights recent studies of mRNA localization in vascular plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 144 publications
0
44
0
Order By: Relevance
“…VDAC3 mRNA targeting does not change the efficiency of VDAC3 protein import [7]. A hypothesis for VDAC3 mRNA localization at MOM is that it could favor a specific localization of the protein into particular MOM microdomains or specific interactions with other proteins, similar to that proposed for prolamin and glutelin mRNAs at the endoplasmic reticulum [34]. VDAC3, more than any other VDAC, has been shown to interact with different proteins such as glycolytic enzymes [35,36], proteins involved in ROS response [26,37] or proteins associated with cytoskeleton [38].…”
Section: Discussionmentioning
confidence: 75%
“…VDAC3 mRNA targeting does not change the efficiency of VDAC3 protein import [7]. A hypothesis for VDAC3 mRNA localization at MOM is that it could favor a specific localization of the protein into particular MOM microdomains or specific interactions with other proteins, similar to that proposed for prolamin and glutelin mRNAs at the endoplasmic reticulum [34]. VDAC3, more than any other VDAC, has been shown to interact with different proteins such as glycolytic enzymes [35,36], proteins involved in ROS response [26,37] or proteins associated with cytoskeleton [38].…”
Section: Discussionmentioning
confidence: 75%
“…This is particularly uncertain in P. peruviana which currently lacks a reference genome sequence. Thus, plants present a large variety of mRNAs which can be very related and induced to the wrong amplification ( Tian et al, 2020 ). In this study, from the 17 primer pairs designed, eight showed a high efficiency and were selected for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…In rice endosperm, it was shown that two zipcode RBPs binding glutelin mRNA form a quaternary structure with two membrane fusion factors [ 102 ]. RBP-P and RBP-L, as discussed in Section 2.1.1 , participate in the coopting of endosomal trafficking for mRNA translocation [ 103 , 104 ]. Mutant lines of RBP-P proteins in rice showed mis-localized glutelin and prolamine mRNAs (coding for the two most prominent seed storage proteins), as well as altered regulation of biological processes during seed development [ 104 ].…”
Section: Rna-protein Interactions In Plants As Unearthed By Classimentioning
confidence: 99%